2019
DOI: 10.1002/jcp.29168
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐methylation‐mediated silencing of miR‐7‐5p promotes gastric cancer stem cell invasion via increasing Smo and Hes1

Abstract: Cancer stem cells are undifferentiated cancer cells that have self-renewal ability, a high tumorigenic activity, and a multilineage differentiation potential. MicroRNAs play a critical role in regulating gene expression during carcinogenesis. Here, we investigated the role of miR-7 and the mechanism by which it is dysregulated in gastric cancer stem cells (GCSCs). The stem cell marker, CD44, was used to sort GCSCs by fluorescence-activated cell sorting. We found that CD44 (+) cells have higher invasiveness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Moreover, it has been shown that miR-7 is associated with the progression of various tumors, including gastric cancer, lung cancer, breast cancer, and glioma [11]. DNA methylation-mediated miR-7-5p silencing would promote the gastric cancer stem cell invasion by increasing Smo and Hes1 [12]. Furthermore, methylation of miR-7 can be used as a biomarker for predicting the poor survival in patients with non-small cell lung cancer at the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that miR-7 is associated with the progression of various tumors, including gastric cancer, lung cancer, breast cancer, and glioma [11]. DNA methylation-mediated miR-7-5p silencing would promote the gastric cancer stem cell invasion by increasing Smo and Hes1 [12]. Furthermore, methylation of miR-7 can be used as a biomarker for predicting the poor survival in patients with non-small cell lung cancer at the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research studies have unveiled that aberrant DNA Abbreviations 5-aza-dC, 5-aza-2ʹ-deoxycytidine; CGI, CpG island; DEmRNA, differentially expressed mRNA; FC, fold change; HCC, hepatocellular carcinoma; MSP, methylation-specific PCR; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide; NC, negative control; PZP, pregnancy zone protein; SD, standard deviation; TCGA-LIHC, The Cancer Genome Atlas Liver Hepatocellular Carcinoma. methylation is able to facilitate tumor cell proliferation, invasion and migration of colorectal cancer [8], gastric cancer [9], liver cancer [10,11], HCC [12] and so on.…”
mentioning
confidence: 99%
“…miR-7 has been found in recent years to serve as a tumor suppressor in several tumor types, but its role in GC has not previously been demonstrated. Recent reports showed that miR-7 plays a certain role in gastric cancer and can be regulated by Circular RNA, long non-coding RNA or DNA methylation (Pan et al, 2018;Yang et al, 2018;Xin et al, 2020). Herein, we found miR-7 to be expressed at lower levels in GC tumors, and when overexpressed miR-7 inhibited the proliferation and glycolytic metabolism of GC cells, in addition to increasing their cisplatin sensitivity.…”
Section: Discussionmentioning
confidence: 64%